TINJAUAN PUSTAKA: PEMANFAATAN TANAMAN BERKHASIAT ANTI AGING (ANTI PENUAAN) INDONESIA - Sinurat, Elisabet Putriana; Diningrat, Diki Setya (Pattimura University, 2023)
This study aims to determine the availability and quantity of literature regarding the use of antiaging plants obtained from the Google Scholar, Scopus, Pubmed and IPB Scientific Repository databases. The research design used is a literature review research design or literature review. Data collection techniques were carried out through literature searches on 4 different databases, namely: Google Scholar, Scopus, PubMed and IPB Scientific Repository. The results showed that there were 999 articles on the use of antiaging plants in the Google Scholar database, 200 articles on Scopus, 2,371 articles on PubMed, and 661 articles on the IPB Scientific Repository, bringing the total to 4,231 articles. After going through a complete process of screening and evaluating articles, 24 articles were obtained that met the search criteria. Based on the complete review process of the 24 articles, 24 types of plants were obtained that have the potential to be used as anti-aging, namely moringa, rosella flowers, shallots, purslane, green tea, nutmeg, arabica coffee, black soybeans, pagoda, patchouli, Dayak onions, potatoes, aloe vera, kaffir lime, yellow passion fruit, malaka, corn, raspberries, wungu, jernang rattan, pegagan, merbau, grapes, and pineapple.